Improving The Health of Special Groups (Elderly, Women and Children) through Community Empowerment in Ulidang Village - Irwan, Muhammad; Irfan, Irfan; Harli, Kurnia; Risnah, Risnah (PABBURA : Health Service Journal, 2024)
This article discusses efforts to improve the health of special groups, namely the elderly, women and children, through community service programs in Ulidang Village. The main aim of this activity is to empower local communities in an effort to improve the health level of these vulnerable groups. A participatory approach is used in program planning and implementation, actively involving all levels of society, including community leaders, village government and local groups. This program carries out health education activities, training in healthy living skills, and strengthening the role of families in supporting the health of members of special groups who are in transitional life situations. Apart from that, efforts are also being made to increase the accessibility of health services, including health facilities. During implementation, monitoring and evaluation is carried out to measure the positive impact of community empowerment activities on the health of special groups. It is hoped that the results of this activity will be able to increase public knowledge, focusing on special groups, namely the elderly, women and children, regarding the importance of health, increase active community involvement in efforts to prevent disease, and provide a positive impact on the health of the elderly, women and children in Ulidang Village. This article contributes to the understanding and implementation of the community empowerment model as an effective strategy for improving the health of specific groups in the village context.